EVALUASI SISTEM PENERANGAN JALAN H.R. SOEBRANTAS KOTA PEKANBARU - Hamzah Hamzah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2008)
The using of road light which is inappropriate for road category and the illegal street light are the two main problem of roadway lighting (PJU). These problems encumber the budget paid by local government (Pemda). Local government paid electric energy for PJU based on the usage of electricity recorded by KWH meter. Meanwhile the payload of the varied roadway lightings without KWH meter will be calculated based on basic monthly rate according to name plate of power and type of the lamp. Local government applies the roadway lighting taxes (PPJU) collected by state company (PLN) from every customers based on percentage of monthly expenses of electricity. Along with the growth of town, there would be more roadways to be illuminated. It will increase the payment of electricity for roadway lighting in every each town and sub-province. This condition would progressively burden the government to settle the expense of electricity for PJU. Therefore, the existing roadway lighting system should be re-evaluated to increase efficiency of electrical usage. In additional, this evaluation will give contribution to save the budget for the roadway lighting electrical payment and with the same existing cost more roadways will get lighting.